Femoral pseudoaneurysm rupturing into urinary bladder: A rare presentation - Shrestha, Kajan Raj (J Surg Case Rep, 2015)
Femoral pseudoaneurysm is a common occurrence in intravenous drug abuser due to repeated trauma to the femoral artery causing arterial leak contained by the surrounding tissue and does not contain all the layers of arterial wall. Rupture of these aneurysm to exterior is a common presentation while rupture into surrounding structure deemed an emergency surgical attention. Hence, we report an unusual case of rupture of femoral pseudoaneurysm into urinary bladder who presented us with history of hematuria and was successfully managed.